Whole transcriptomic and proteomic analyses of an isogenic M. tuberculosis clinical strain with a naturally occurring 15 Kb genomic deletion. - Carla Duncan; Frances B Jamieson; JoLynn Troudt; Linda Izzo; Helle Bielefeldt-Ohmann; Angelo Izzo; Carolina Mehaffy (PLoS ONE, 2017)
Tuberculosis remains one of the most difficult to control infectious diseases in the world. Many different factors contribute to the complexity of this disease. These include the ability of the host to control the infection which may directly relate to nutritional status, presence of co-morbidities and genetic predisposition. Pathogen factors, in particular the ability of different Mycobacterium tuberculosis strains to respond to the harsh environment of the host granuloma, which includes low oxygen and nutrient availability and the presence of damaging radical oxygen and nitrogen species, also play an important role in the success of different strains to cause disease. In this study we evaluated the impact of a naturally occurring 12 gene 15 Kb genomic deletion on the physiology and virulence of M. tuberculosis. The strains denominated ON-A WT (wild type) and ON-A NM (natural mutant) were isolated from a previously reported TB outbreak in an inner city under-housed population in Toronto, Canada. Here we subjected these isogenic strains to transcriptomic (via RNA-seq) and proteomic analyses and identified several gene clusters with differential expression in the natural mutant, including the DosR regulon and the molybdenum cofactor biosynthesis genes, both of which were found in lower abundance in the natural mutant. We also demonstrated lesser virulence of the natural mutant in the guinea pig animal model. Overall, our findings suggest that the ON-A natural mutant is less fit to cause disease, but nevertheless has the potential to cause extended transmission in at-risk populations.